Blockchain-Based Leadership: How Blockchain Technology Enhances Transparency and Accountability in Organizational Leadership - Ari Akbar; Djamaliyah Djamaliyah; Nur Aisyah; Mochammad Isa Anshori (Jurnal Ilmiah Manajemen Kesatuan, 2025)
The main objective of this study is to identify, analyze, and synthesize literature related to blockchain integration in leadership practices. The search methodology was conducted through major electronic databases with relevant keywords, resulting in 45 articles that met the inclusion criteria for further analysis. The results of the analysis revealed five main themes, namely Decentralization of Leadership Authority, Transparency and Accountability, DAO (Decentralized Autonomous Organization) Leadership Model, Transformation of Trust in Leadership, and Challenges of Implementation and Adoption. Blockchain technology has the potential to transform traditional leadership systems by creating a more transparent, efficient, and distributed trust-based environment. However, the implementation of blockchain-based policies faces various challenges, including technical barriers, organizational culture, and regulatory barriers. This study contributes to the understanding of how blockchain technology can change the dynamics of leadership and organizational governance. In addition, the findings of this study offer insights for further research in developing more adaptive, innovative, and sustainable leadership models in the digital era.